Efficient Access to Enantiopure γ4‐Amino Acids with Proteinogenic Side‐Chains and Structural Investigation of γ4‐Asn and γ4‐Ser in Hybrid Peptide Helices. Issue 48 (21st October 2013) - Jadhav, Sandip V.; Misra, Rajkumar; Singh, Sumeet K.; Gopi, Hosahudya N.
Abstract Hybrid peptides composed of α‐ and β‐amino acids have recently emerged as new class of peptide foldamers. Comparatively, γ‐ and hybrid γ‐peptides composed of γ4‐amino acids are less studied than their β‐counterparts. However, recent investigations reveal that γ4‐amino acids have a higher propensity to fold into ordered helical structures. As amino acid side‐chain functional groups play a crucial role in the biological context, the objective of this study was to investigate efficient synthesis of γ4‐residues with functional proteinogenic side‐chains and their structural analysis in hybrid‐peptide sequences. Here, the efficient and enantiopure synthesis of various N‐ and C‐terminal free‐γ4‐residues, starting from the benzyl esters (COOBzl) of N‐Cbz‐protected (E)‐α, β‐unsaturated γ‐amino acids through multiple hydrogenolysis and double‐bond reduction in a single‐pot catalytic hydrogenation is reported. The crystal conformations of eight unprotected γ4‐amino acids (γ4‐Val, γ4‐Leu, γ4‐Ile, γ4‐Thr(OtBu), γ4‐Tyr, γ4‐Asp(OtBu), γ4‐Glu(OtBu), and γ‐Aib) reveals that these amino acids adopted a helix favoring gauche conformations along the central CγCβ bond. To study the behavior of γ4‐residues with functional side chains in peptide sequences, two short hybrid γ‐peptides P1 (Ac‐Aib‐γ4‐Asn‐Aib‐γ4‐Leu‐Aib‐γ4‐Leu‐CONH2) and P2 (Ac‐Aib‐γ4‐Ser‐Aib‐γ4‐Val‐Aib‐γ4‐Val‐CONH2) were designed, synthesized on solid phase, and their 12‐helical conformation in single crystals were studied. Remarkably, the γ4‐Asn residue in P1 facilitates the tetrameric helical aggregations through interhelical H bonding between the side‐chain amide groups. Furthermore, the hydroxyl side‐chain of γ4‐Ser in P2 is involved in the interhelical H bonding with the backbone amide group. In addition, the analysis of 87 γ4‐residues in peptide single‐crystals reveal that the γ4‐residues in 12‐helices are more ordered as compared with the 10/12‐ and 12/14‐helices.